Efikasi Diri Pengambilan Keputusan Karier pada Mahasiswa: Analisis Perbedaan Gender di Provinsi Jawa Tengah - Leoni Amalia Yanli; William Gunawan (Humanitas (Jurnal Psikologi), 2025)
This study aims to examine differences in career decision-making self-efficacy between male and female undergraduate students in Central Java Province. A quantitative approach was employed using secondary data from the Membangun Generasi Muda Mandiri (MGMM) study, which applied a stratified quota sampling technique. The study involved 173 male and 305 female respondents from 15 universities, with the majority being at the senior class level (132 males and 243 females). Measurement was conducted using the Indonesian-adapted Short Form of the Career Decision-Making Self-Efficacy Scale, which consists of five dimensions: goal setting, gathering occupational information, problem solving, planning, and self-appraisal. Data analysis was conducted using an Independent Samples t-Test, taking into account the large sample size and the data distribution that was practically close to normal. The findings revealed that there were no significant differences in career decision-making self-efficacy based on gender. Although dimensional-level analysis indicated a near-significant difference in the Goal Setting dimension, the small effect size (r < 0.1) indicates that this difference is not practically meaningful. Overall, the results demonstrate that male and female students exhibit relatively comparable levels of career decision-making self-efficacy, in which gender is no longer a primary determining factor in the development of career decision-making self-efficacy.